ABORSI DALAM PERSPEKTIF HUKUM ISLAM - Yusriana Yusriana (Jurnal Ilmiah Penegakan Hukum, 2015)
Abortion is an act to terminate a pregnancy by removing the fetus from thewomb before the fetus can survive outside content. In general, women hadabortions because it led some of them economic incentive / motivation individually,beauty boost, boost morale and motivation within. According to Islamic law inprinciple prohibited abortion illegal. But for certain conditions with a number ofother reasons allowed in medical and Syar'i, then abortion can be performed.